1994
DOI: 10.2105/ajph.84.6.977
|View full text |Cite
|
Sign up to set email alerts
|

Social influences on the sexual behavior of youth at risk for HIV exposure.

Abstract: OBJECTIVES. Adolescents are increasingly at risk for infection with human immunodeficiency virus (HIV) and other sexually transmitted diseases, especially in poor urban minority communities. To aid the design of interventions in these communities, this study investigated the role of knowledge, attitudes, perceived parental monitoring, and peer behavior in the onset and progression of sexual behavior in children at risk for exposure to HIV. METHODS. A computerized personal interview was administered to 300 Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
170
1
14

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(196 citation statements)
references
References 21 publications
11
170
1
14
Order By: Relevance
“…[9][10][11] American Indian youth are no exception. 3 Among sexually active youth the number of sexual partners, substance use during sex, and not using condoms have been associated with HIV/AIDS infection.…”
Section: Sexual Behavior and Hiv/aidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] American Indian youth are no exception. 3 Among sexually active youth the number of sexual partners, substance use during sex, and not using condoms have been associated with HIV/AIDS infection.…”
Section: Sexual Behavior and Hiv/aidsmentioning
confidence: 99%
“…Knowledge and attitudes do not consistently predict behavior. 2,10,[26][27][28][29][30][31] The inconsistent findings have been explained, in part, in terms of a failure to account for context. A person's ability to translate knowledge and norms into healthy behavior may be encouraged or constrained by contextual factors.…”
mentioning
confidence: 99%
“…Instrumental parenting characteristics such as permissiveness and monitoring are also related to teens' sexual experience. Later sexual debut is associated with more parental monitoring, less parental permissiveness, and the presence of household routines and rules (Danziger, 1995;Li et al, 2000;Metzler et al, 1994;Miller et al, 1998Miller et al, , 1999Romer et al, 1994Romer et al, , 1999. Parental monitoring reduces opportunities for early sexual activity by limiting adolescents' exposure to sexual possibility situations (Paikoff, 1995).…”
Section: Parenting Stylesmentioning
confidence: 99%
“…In addition, a number of studies have found that perceptions of peers' sexual attitudes and behaviors predict sexual risk behavior among teenagers. [13][14][15] Teenagers who sext may hold similar beliefs, perceiving their peers, parents, and even the media to approve of sexual activity. Sexting may also relate to difficulties with managing emotions.…”
mentioning
confidence: 99%